EPIC MODEL: EFEKTIVITAS IKLAN DESTINASI WISATA KABUPATEN BANYUWANGI TERHADAP MINAT BERKUNJUNG ULANG WISATAWAN DOMESTIK - Ika Barokah Suryaningsih; Kristian Suhartadi Widi Nugraha (Management Insight: Jurnal Ilmiah Manajemen, 2018)
Visiting a tourist destination is influenced by advertising through the internet, for example, facebook, Instagram, traveler blogger, kaskus, and so on. All tourism promotion processes are carried out online, so that tourists can search everything about tourist destinations that will be addressed wherever and whenever comfortably. This can foster interest in revisiting tourists for tourist destinations in Banyuwangi Regency. This study aims to determine the effectiveness of online advertising in all tourist destinations in Banyuwangi Regency, both nature-based tourism and Banyuwangi art-based tourism. Methods of data collection in this study using survey of all tourists who provide testimonials or expressions of tourism in Banyuwangi through online media. It is tourists who intend to visit tourist destinations in Banyuwangi Regency. Primary data is obtained from the results of questionnaires distributed to respondents distributed online through google.doc. The data analysis technique uses the EPIC method model which consists of four dimensions namely empathy, persuasion, impact and communication. Processing data to get the results of advertising effectiveness is used simple tabulation analysis, mean score, and EPIC rate. Based on the results of EPIC rate analysis, the EPIC rate value is 3.66 which if included in the EPIC rating scale Model is included in the effective category. Thus the advertisement of tourist destinations in Banyuwangi Regency is done using online media effectively against the interest of revisiting domestic tourists.